Warranty Data Collection and Analysis - Blischke, Wallace R.; Karim, M. Rezaul; Murthy, D. N. Prabhakar; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2011)
Warranty Data Collection and Analysis deals with warranty data collection and analysis and the problems associated with these activities. The book is a both a research monograph and a handbook for practitioners. As a research monograph, it unifies the literature on warranty data collection and analysis, and presents the important results in an integrated manner. In the process, it highlights topics that require further research. As a handbook, it provides the essential methodology needed by practitioners involved with warranty data collection and analysis, along with extensive references to further results. Models and techniques needed for proper and effective analysis of data are included, together with guidelines for their use in warranty management, product improvement, and new product development. Warranty Data Collection and Analysis will be of interest to researchers (engineers and statisticians) and practitioners (engineers, applied statisticians, and managers) involved with product warranty and reliability. It is also suitable for use as a reference text for graduate-level reliability programs in engineering, applied statistics, operations research, and management.
1. An Overview -- 2. Product Warranty -- 3. Reliability -- 4. Warranty Claims Data -- 5. Supplementary Warranty Data -- 6. Cost Models for One-Dimensional Warranties -- 7. Cost Models for Two-Dimensional Warranties -- 8. Preliminary Data Analysis -- 9. Basic Statistical Inference -- 10. Additional Statistical Techniques -- 11. Nonparametric Approach to the Analysis of 1-D Warranty Data -- 12. Parametric Approach to the Analysis of 1-D Warranty Data -- 13. Complex Models for Parametric Analysis of 1-D Warranty Data -- 14. Analysis of 2-D Warranty Data -- 15. Use of Warranty Data for Improving Current Products and Operations -- 16. Role of Warranty Data in New Product Development -- 17. Case Study 1: Analysis of Air Conditioner Claims Data -- 18. Case Study 2: Analysis of Automobile Components Warranty Claims Data.
Keywords: Engineering; Engineering economics; Engineering economy; Quality control; Reliability; Industrial safety; Industrial organization; Engineering; Quality Control, Reliability, Safety and Risk; Engineering Economics, Organization, Logistics, Marketing; Industrial Organization; Electronic books